PENDAMPINGAN METODE MUSĀBAQAH BIṬĀQAH MUKHTALIṬUL KALIMAH DALAM PEMBELAJARAN BAHASA ARAB DI PONDOK PESANTREN DARUSY SYAHADAH BOYOLALI - Nurul Latifatul Inayati; Umi Nur Kasanah; Kusnul Khotimah (Jurnal Pengabdian Masyarakat Nusantara, 2021)
Learning strategies/methods are very important in learning. Errors in the selection of strategies/learning methods can be a barrier to the course of teaching and learning activities (KBM). Arabic is one of the subjects that is highly emphasized in Darusy Syahadah Islamic boarding school. The ability of the Arabic language for a santri is like a weapon that they will use in battle to search for and explore the Islamic sciences. However, in his journey there were several problems encountered in learning Arabic, including the emergence of drowsiness and boredom that befell students while attending Arabic learning. With these problems, it is necessary to have community service activities in order to create a more creative and attractive learning atmosphere for students. The purpose of this community service activity is to provide assistance in the application of the MusÄbaqah Biá¹Äqah Mukhtaliá¹ul Kalimah method in learning Arabic. The implementation method in this community service activity includes four stages, namely the planning stage, the implementation phase, the observation and evaluation stage, and finally the reflection phase. With the application of the MusÄbaqah Biá¹Äqah Mukhtaliá¹ul Kalimah method, it is proven that it can increase the activeness and enthusiasm of student learning which impacts on increasing student learning outcomes. So the development of the MusÄbaqah Biá¹Äqah Mukhtaliá¹ul Kalimah method as well as other active learning methods is very necessary in order to increase student interest in learning.